Chattering-free adaptive fast convergent terminal sliding mode controllers for position tracking of robotic manipulators. (March 2016) - He, Shaoming; Lin, Defu; Wang, Jiang
The paper documents a new continuous adaptive fast terminal sliding mode control approach for position tracking of robotic manipulators. Combining linear sliding mode and terminal sliding mode, a fast nonsingular terminal sliding mode manifold is presented. Considering the discontinuous property of the sign function, which is often used in traditional sliding mode controller and will result in high-freqsency chattering in the control channel, the proposed controller adopts the continuous saturation function for chattering elimination. Besides the continuous property, convergence to the origin asymptotically and in finite time can be guaranteed in theory with the proposed controller, which is quite different from traditional boundary layer technique, where only bounded motion around the sliding manifold can be ensured. For asymptotic stability, it is only required that the lumped uncertainty is bounded, but the upper bound may be unknown by virtue of the designed adaptive methodology. The obtained results are applied to the problem of position tracking for robotic manipulators. Detailed simulations with some comparisons under various conditions demonstrate the effectiveness of the proposed method.